Modernization of a Legacy System as Microservices - Kostian, Mikael (My University, 2018)
This thesis is about modernizing a monolithic legacy system as microservices. Modernization is often as much about technological advancements as it is about answering to requirements which a legacy system is not able to meet. Concurrently, modernization should lead to improvements in software engineering practices which play a key role in the design and implementation of high quality systems. Thesis is built around an on-going modernization project at Hesburger, a Finnish fast food restaurant chain, aiming to replace a business-critical legacy system while improving efficacy, scalability, reliability and maintainability. Modernization strategies, microservice architecture and a model to build microservices around business capabilities are outlined. A modernization plan based on existing modernization strategies is formulated for the Hesburger legacy system. A prototype consisting of sales related microservices, extracted by analysing the legacy system and business capabilities, is built to demonstrate the effectiveness of the devised modernization plan.
Keywords: legacy system modernization, modernization strategies, microservices